Security problems for a pseudorandom sequence generator based on the Chen chaotic system - Ozkaynak, Fatih; Yavuz, Sirma (ELSEVIER SCIENCE BV, 2013)
Recently, a novel pseudorandom number generator scheme based on the Chen chaotic system was proposed. In this study, we analyze the security weaknesses of the proposed generator. By applying a brute force attack on a reduced key space, we show that 66% of the generated pseudorandom number sequences can be revealed. Executable C# code is given for the proposed attack. The computational complexity of this attack is O(n), where n is the sequence length. Both mathematical proofs and experimental results are presented to support the proposed attack. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Chaos; Cryptography; Pseudorandom number generator; Cryptanalysis; IMPROVED HYPERCHAOTIC SEQUENCES; IMAGE ENCRYPTION; CIPHERS; MAPS; Computer Science; Physics